An Analysis of the Impact of the Covid-19 Pandemic on the Implementation of Renewable Energy in the Supply of Electricity - Al Hasibi, Rahmat Adiprasetya; Bawan, Elias Kondorura (International Journal of Sustainable Energy Planning and Management, 2023)
The Covid-19 pandemic has affected all activities, including the electricity supply. As a developing nation, Indonesia is also severely affected by the diversion of significant resources to combat Covid-19. On the other hand, Indonesia is committed to reducing emissions in the energy sector, which includes implementing renewable energy technologies to provide electricity. This article examines the effect of the post-covid-19 pandemic situation on the implementation of renewable energy in the electricity supply. The case study examined is the electricity supply in the province of Yogyakarta, which obtains its electricity from outside the province but has multiple forms of renewable energy that can be optimized in the electricity supply. There are three scenarios discussed: the current target scenario, the lower target scenario, and the supply security scenario. The current target scenario includes predetermined renewable energy goals. The lower target scenario is used to characterize Covid-19's impact on the implementation of renewable energy. The supply security scenario is the most optimistic, as it optimizes the use of renewable energy in the electricity supply while ignoring the impact of the co-19 pandemic. The current target scenario is used as a benchmark against which the other two scenarios are compared. Comparing the lower target scenario to the current target scenario, the lower target scenario results in 9.6% lower capital costs and 4.1% higher greenhouse gas emissions. The least greenhouse gas emissions are produced by the supply security scenario, but the capacity costs are the highest.